Cyclization of o-Alkynylisocyanobenzenes with 1,3-Dicarbonyl Compounds - Kannika La-Ongthong (2022)
A facile and convenient reaction of o-alkynylisocyanobenzenes with various active-methylene compounds, including 1,3-diesters, 1,3-diketones, β-keto esters, and β-keto amides, under Brønsted basic conditions, has been developed. Diethyl malonate reacted smoothly with a collection of o-alkynylisocyanobenzenes to provide the corresponding 2-quinolin-2-yl malonates in excellent yields. Acetylacetone gave a mixture of quinolin-4-yl and quinolin-2-yl derivatives. Acetoacetate esters and acetoacetyl amide derivative initially gave 2-quinolin-2-yl adducts that underwent partial deacetylation under the reaction conditions.